A research-inducing environment at a University of Technology in South Africa: Challenges and future prospects. (August 2019) - Mtshali, Mduduzi Nkosinathi Gladwin; Sooryamoorthy, Radhamany
Highlights: The study is of one University of Technology in South Africa which has been transformed from a technikon. It examines the research-inducing environment in a University of Technology (UoT). It presents empirical data regarding various aspects of their research environment. The study presents strategies that can be adopted to improve the research environment in UoTs. It provides a future-oriented perspective of the research environment in UoTs. Abstract: Universities of Technology (UoTs) are a new addition to the higher education sector in South Africa. In the wake of the political changes from apartheid to democracy, South Africa went ahead with reforms in the higher education system. The transformation of technikons to UoTs was one major step in this regard. Historically, technikons had challenges in maintaining a research profile. An observable research culture was lacking in these technikons which accompanied them when they were made into UoTs. This has implications not only for the UoTs but also for the higher education sector in the country. This empirical study of one such University of Technology examines the research-inducing environment in terms of its presence in the current institutional set up, the strategies that are meant to incentivise research activities and the future of UoTs. The study presents the data collected from the academic staff working in the selected University of Technology in South Africa. Apart from revealing prevailing aspects of the research environment, the study provides a view to the future of UoTs in the higher education sector in the country.